Intracellular Lipid Accumulation Drives the Differentiation of Decidual Polymorphonuclear Myeloid-Derived Suppressor Cells via Arachidonic Acid Metabolism - Wang, Qiaohong; Zhang, Xinyang; Li, Congcong; Xiong, Miao; Bai, Wenxin; Sun, Si; Chen, Chao; Zhang, Xiaoxin; Li, Mingyang; Zhao, Aimin (Frontiers in Immunology, 2022)
Decidual polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) are essential to immune tolerance during pregnancy. A reduction in the number of these cells is associated with unexplained recurrent pregnancy loss (URPL). In our previous study, we reported that PMN-MDSCs are a group of mature neutrophils that are activated by the decidua microenvironment. In the present study, we show that the decidua microenvironment induces substantial lipid accumulation in neutrophils during their differentiation to PMN-MDSCs. Lower levels of lipid accumulation are detected in PMN-MDSCs from URPL patients, and the amount of lipid in the PMN-MDSCs is positively correlated with the proportion of PMN-MDSCs. Next, we demonstrate that decidua-derived IL6 with the presence of arachidonic acid, upregulates fatty acid binding protein 5 (FABP5) via the phosphorylation of signal transducer and activator of transcription 3 (STAT3). FABP5 then continuously stimulates intracellular lipid accumulation. Increased intracellular lipid accumulation mediates arachidonic acid metabolism, a pathway that is significantly activated by the induction of the decidua microenvironment, to stimulate the synthesis of prostaglandin E2 (PGE2) and finally induce the differentiation of PMN-MDSCs. To summarize, decidua-derived IL6 facilitates the differentiation of PMN-MDSCs from neutrophils via the pSTAT3/FABP5/PGE2 pathway. Defects in the process may result in impaired differentiation and dysfunction of PMN-MDSCs in URPL. These findings enhance our understanding of the physiological mechanisms of immune tolerance in pregnancy and provide therapeutic options for URPL.